New marine amphipod records on the Algerian coast. (4th March 2014) - Bakalem, Ali; Dauvin, Jean-Claude; Grimes, Samir
Abstract : Recent sampling surveys (2011–2012) of the shallow (0–50 m) hard-bottom communities and re-examination of some soft-bottom communities (5–143 m) along the Algerian coast have allowed the collection of 33 species (five Caprelloidea, 27 Gammaridea and one Hyperiidea), which were not recorded before in the inventory of the marine amphipod fauna of Algeria (Bakalem & Dauvin, 1995; Grimes et al., 2009). This paper reports the number of specimens sampled for each of these 33 species and provides data on their geographical distribution and habitats. Fourteen of the species (43%) are considered to be endemic to the Mediterranean Sea; 15 others are north-eastern Atlantic and Mediterranean species, and the four last are cosmopolitan species. Twenty-nine of the new records are known for Italian waters and 19 in Greek waters where there is intensive amphipod inventory. The total number of marine amphipod fauna in Algeria is now 332.